Pengukuran Kualitas Aplikasi E-Surat Menggunakan ISO 9126 - Rahmat Musfikar; Liza Rozana; Hazrullah Hazrullah; Raihan Islamadina (PTE FTK UIN Ar-Raniry, 2023)
Electronic mail is a web-based tool that is used to archive incoming and outgoing letters. This application was created to help and expedite the job of filing letters at SMK Muhammadiyah Banda Aceh. Defects are common in any new software development; development allows for errors to make the application heavier. As a result, testing software is critical; the purpose is to determine the quality of the information system that has been built or developed, because quality affects user happiness. A standard is required in the construction and development of a quality information system so that the feasibility of the information system can be measured. The International Organization for Standardization (ISO) 9126 standard is used in this study's quality assessment. The results reveal that the built web-based document archiving information system satisfied the ISO 9126 criteria in terms of functionality, usability, dependability, and efficiency.